Goose barnacle Pollicipes pollicipes as biomonitor of metal contamination in the northwest coast of Portugal - Pedro A Reis (2012)
The main objective of this work was to assess the potential use of goose barnacle Pollicipes pollicipes as biomonitor of metal contamination in northwest (NW) coast of Portugal. The concentrations of Cd, Cr, Cu, Fe, Mn, Ni and Zn were determined in coastal seawaters and tissues of P. pollicipes, which allowed establishing correlations between metals in coastal seawaters and P. pollicipes and calculating metal bioaccumulation factors (BAFs). The results of this study showed that P. pollicipes soft tissues can be used for monitoring metal contamination in these coastal seawaters: (1) there were significant correlations (p < 0.05) between metals in soft tissues and their concentrations in seawaters, except for Zn (p > 0.05); (2) soft tissues were sensitive to spatial variations of metal bioavailabilities and their concentrations ranged 0.70-2.22 mg Cd kg(-1), 0.49-1.40 mg Cr kg(-1), 1.37-2.07 mg Ni kg(-1), 2.4-3.3 mg Cu kg(-1), 5-59 mg Mn kg(-1), 134-578 mg Fe kg(-1)and 728-1,854 mg Zn kg(-1); (3) mean logarithmic bioaccumulation factors (log BAF) of Fe, Cd and Zn were higher, 5.57, 5.47 and 4.41, respectively, than mean log BAFs of Cr, Mn, Cu and Ni, 4.18, 4.14, 3.98 and 3.51, respectively. In contrary, P. pollicipes shell plates were not considered ideal material to monitor metal bioavailabilities in these coastal seawaters. Regarding the very high concentrations of Zn obtained in the coastal seawaters and P. pollicipes soft tissues, the NW coast of Portugal should be classified as "Class III/IV - Remarkably/Highly Polluted".